An Analysis of Personal Deixis Used by The Main Character in The La La Land Movie - Binti Qani'ah; Santy Firdatul Islamiyah (English Study Program University of Pasir Pengaraian, 2021)
This research focused on analyzing personal deixis. It was in pragmatics scope. There were two aims in this research. First was to identify what categories of personal deixis are used by the main character in La la land movie. Second was to explain why the most dominant category of personal deixis is used by the main character in La la land movie. A descriptive qualitative method was in this research. The data of this research were utterances that consist of personal deixis. Then, the source of data was La la land movie. The results of this research were the main character used three categories of personal deixis in La la land movie. They were first personal deixis found 43 data, second personal deixis found 23 data, and third personal deixis found 20 data. The total data were 85 data. The most dominant category used by the main character in La la land movie was first personal deixis. The main character often used first personal deixis in this movie. It was because it represented Sebastian’s struggles to solve his problems of his life, such as finding a job as a jazz pianist, reaching his dreams in Los Angeles as the famous jazz musician and had his own jazz club.